Effect of donor nephrectomy time during circulatory‐dead donor kidney retrieval on transplant graft failure. Issue 1 (1st October 2019) - Heylen, L.; Pirenne, J.; Samuel, U.; Tieken, I.; Coemans, M.; Naesens, M.; Sprangers, B.; Jochmans, I.
Abstract : Background: When the blood supply ceases in a deceased organ donor, ischaemic injury starts. Kidneys are cooled to reduce cellular metabolism and minimize ischaemic injury. This cooling is slow and kidneys are lukewarm during nephrectomy. Smaller single‐centre studies have shown that prolonged donor nephrectomy time decreases early kidney transplant function, but the effect on long‐term outcome has never been investigated in large multicentre cohort studies. Methods: The relationship between donor nephrectomy time and death‐censored graft survival was evaluated in recipients of single adult‐to‐adult, first‐time deceased‐donor kidneys transplanted in the Eurotransplant region between 2004 and 2013. Results: A total of 13 914 recipients were included. Median donor nephrectomy time was 51 (i.q.r. 39–65) min. Kidneys donated after circulatory death had longer nephrectomy times than those from brain‐dead donors: median 57 (43–78) versus 50 (39–64) min respectively ( P  < 0·001). Donor nephrectomy time was independently associated with graft loss when kidneys were donated after circulatory death: adjusted hazard ratio (HR) 1·05 (95 per cent c.i. 1·01 to 1·09) per 10‐min increase ( P  = 0·026). The magnitude of this effect was comparable to the effect of each hour of additional cold ischaemia: HR 1·04 (1·01 to 1·07) per h ( P  = 0·004). For kidneys donated after brain death, there was no effect of nephrectomy time on graft survival: adjusted HR 1·01 (0·98 to 1·04) per 10 min ( P  = 0·464). Conclusion: Prolonged donor nephrectomy time impairs graft outcome in kidneys donated after circulatory death. Keeping this short, together with efficient cooling during nephrectomy, might improve outcome. Abstract : This study of the Eurotransplant registry covering 13 914 kidney transplants demonstrated that donor nephrectomy time impairs graft outcome in kidneys donated after circulatory death, but not in kidneys donated after brain death. Quicker the better Abstract : Antecedentes: La lesión por isquemia empieza en el momento que cesa la irrigación sanguínea del órgano donante. Para reducir el metabolismo celular y la lesión isquémica se reduce la temperatura de los riñones. Este enfriamiento es lento y los riñones se mantienen tibios durante la nefrectomía. Estudios unicéntricos con muestras pequeñas han demostrado que el tiempo de la nefrectomía del donante disminuye la función precoz del injerto renal, pero nunca se ha analizado su repercusión a largo plazo en grandes estudios multicéntricos. Métodos: Se analizó la relación entre la duración de la nefrectomía del donante y la supervivencia del injerto en 13.914 adultos receptores de un primer riñón procedente de donante cadavérico adulto en la región de Eurotransplant entre los años 2004 y 2013. Resultados: La mediana de duración de la nefrectomía del donante fue de 51 minutos (rango intercuartílico 39‐65). En los riñones obtenidos en donantes a corazón parado la duración de la nefrectomía fue más prolongada que en los donantes en muerte cerebral (mediana 57 min (43‐78 min) versus 50 min (39‐64 min), P < 0, 001). La duración de la nefrectomía en el donante se asoció de forma independiente con la pérdida del injerto (cociente de riesgos instantáneos, hazard ratio, HR, ajustado 1, 05 por cada incremento de 10 minutos, i.c. del 95%: 1, 01 a 1, 09; P = 0, 026) cuando los riñones se obtuvieron en donantes en parada cardíaca. La magnitud de este efecto fue comparable al efecto de cada hora adicional de isquemia fría (1, 04, i.c. 95% 1, 01‐1, 07, P = 0, 004). En los riñones obtenidos de donantes en muerte cerebral, la duración de la nefrectomía no influyó en la supervivencia del injerto (HR ajustada 1, 01 por aumento de 10 min, i.c. del 95%: 0, 98 a 1, 04). Conclusión: La duración de la nefrectomía en donantes a corazón parado afecta la función de los injertos trasplantados. Reducir esta duración y disponer de un sistema de enfriamiento eficiente durante la nefrectomía podría mejorar los resultados.